Prognostic model for identifying candidates for hepatectomy among patients with hepatocellular carcinoma and hepatic vein invasion. Issue 7 (4th April 2020) - Zhang, X.‐P.; Wang, K.; Gao, Y.‐Z.; Wei, X.‐B.; Lu, C.‐D.; Chai, Z.‐T.; Zhen, Z.‐J.; Li, J.; Yang, D.‐H.; Zhou, D.; Fan, R.‐F.; Yan, M.‐L.; et al.
Abstract : Background: Hepatic vein tumour thrombus (HVTT) is a major determinant of survival outcomes for patients with hepatocellular carcinoma (HCC). An Eastern Hepatobiliary Surgery Hospital (EHBH)‐HVTT model was established to predict the prognosis of patients with HCC and HVTT after liver resection, in order to identify optimal candidates for liver resection. Methods: Patients with HCC and HVTT from 15 hospitals in China were included. The EHBH‐HVTT model with contour plot was developed using a non‐linear model in the training cohort, and subsequently validated in internal and external cohorts. Results: Of 850 patients who met the inclusion criteria, there were 292 patients who had liver resection and 198 who did not in the training cohort, and 124 and 236 in the internal and external validation cohorts respectively. Contour plots for the EHBH‐HVTT model were established to predict overall survival (OS) rates of patients visually, based on tumour diameter, number of tumours and portal vein tumour thrombus. This differentiated patients into low‐ and high‐risk groups with distinct long‐term prognoses in the liver resection cohort (median OS 34·7 versus 12·0 months; P < 0·001), internal validation cohort (32·8 versus 10·4 months; P = 0·002) and external validation cohort (15·2 versus 6·5 months; P = 0·006). On subgroup analysis, the model showed the same efficacy in differentiating patients with HVTT in peripheral and major hepatic veins, the inferior vena cava, or in patients with coexisting portal vein tumour thrombus. Conclusion: The EHBH‐HVTT model was accurate in predicting prognosis in patients with HCC and HVTT after liver resection. It identified optimal candidates for liver resection among patients with HCC and HVTT, including tumour thrombus in the inferior vena cava, or coexisting portal vein tumour thrombus. Abstract : The Eastern Hepatobiliary Surgery Hospital–hepatic vein tumour thrombus (EHBH‐HVTT) model was accurate in predicting prognosis in patients with hepatocellular carcinoma (HCC) and HVTT after liver resection. It identified optimal candidates for liver resection among patients with HCC and HVTT, including inferior vena cava tumour thrombus, or coexisting portal vein tumour thrombus (PVTT). predicts prognosis Abstract : Antecedentes: La trombosis tumoral de la vena hepática ( hepatic vein tumour thrombus, HVTT) es un determinante importante de los resultados de supervivencia en pacientes con carcinoma hepatocelular ( hepatocellular carcinoma, HCC). Se desarrolló el modelo llamado Eastern Hepatobiliary Surgery Hospital (EHBH)‐HVTT para predecir el pronóstico de los pacientes con HCC y HVTT después de la resección hepática ( liver resection, LR), con el fin de identificar los candidatos óptimos para LR entre estos pacientes. Métodos: Se incluyeron pacientes con HCC y HVTT de 15 hospitales en China. El modelo EHBH‐HVTT con gráfico de contorno se desarrolló utilizando un modelo no lineal en la cohorte de entrenamiento, siendo posteriormente validado en cohortes internas y externas. Resultados: De 850 pacientes que cumplieron con los criterios de inclusión, hubo 292 pacientes en el grupo LR y 198 pacientes en el grupo no LR en la cohorte de entrenamiento, y 124 y 236 en las cohortes de validación interna y externa. Los gráficos de contorno del modelo EHBH‐HVTT se establecieron para predecir visualmente las tasas de supervivencia global ( overall survival, OS) de los pacientes, en función del diámetro del tumor, número de tumores y del trombo tumoral de la vena porta ( portal vein tumour thrombus, PVTT). Esto diferenciaba a los pacientes en los grupos de alto y bajo riesgo, con distinto pronóstico a largo plazo en las 3 cohortes (34, 7 versus 12, 0 meses, 32, 8 versus 10, 4 meses y 15, 2 versus 6, 5 meses, P < 0, 001). En el análisis de subgrupos, el modelo mostró la misma eficacia en la diferenciación de pacientes con HVTT, con trombo tumoral en la vena cava inferior ( inferior vena cava tumour thrombus, IVCTT) o en pacientes con PVTT coexistente. Conclusión: El modelo EHBH‐HVTT fue preciso para la predicción del pronóstico en pacientes con HCC y HVTT después de la LR. Identificó candidatos óptimos para LR en pacientes con HCC y HVTT, incluyendo IVCTT o PVTT coexistente.